Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Retensi Tenaga Pendidik di Lembaga Pendidikan Era Digital - Sulthaan Arrafinur; Bahrani Bahrani (JURNAL MAPPESONA, 2025)
Â This article examines human resource management (HRM) strategies that support teacher retention in educational institutions during the digital era. The study highlights key aspects such as structured career development, performance-based incentives, transformational leadership, and inclusive organizational culture as major contributors to teacher loyalty and job satisfaction. To explore these issues, a literature review method was employed, analyzing relevant empirical and conceptual studies from the past decade. The analysis was conducted through a thematic synthesis approach, focusing on recurring patterns and challenges in HRM practices. Findings indicate that digital tools such as Human Resource Information Systems (HRIS), Learning Management Systems (LMS), and collaborative platforms play a pivotal role in enhancing engagement and streamlining administrative processes. Nonetheless, implementation remains constrained by infrastructure limitations, budgetary issues, digital literacy gaps, and the absence of comprehensive retention policies. This review concludes that adaptive, data-driven, and collaborative HRM strategies are essential to building a supportive educational environment and ensuring sustainable teacher retention in the face of digital transformation.